2015
DOI: 10.1097/pra.0000000000000105
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Urinary Tract Infections (UTIs) and Delirium

Abstract: Urinary tract infections (UTIs) are among the most common bacterial infections. Although comorbid UTI in geriatric patients with delirium or dementia is well known, the prevalence and scope of the association with other neuropsychiatric disorders is unclear. We performed a systematic review of the association between UTIs and delirium, dementia, psychotic disorders, and mood disorders in hospitalized patients. We identified studies by searching PubMed, PsycInfo, and Web of Knowledge, and the reference lists of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 38 publications
0
16
0
Order By: Relevance
“…Urinary tract infections have been described in the setting of various neuropsychiatric conditions including delirium, dementia, psychotic disorders, and mood disorders. A systematic review found that 88% of the articles reviewed in this area demonstrated a positive association between UTI and neuropsychiatric disorders [9]. In addition, 47% of these articles described UTI being involved in exacerbating or even precipitating these conditions [9].…”
Section: Discussionmentioning
confidence: 99%
“…Urinary tract infections have been described in the setting of various neuropsychiatric conditions including delirium, dementia, psychotic disorders, and mood disorders. A systematic review found that 88% of the articles reviewed in this area demonstrated a positive association between UTI and neuropsychiatric disorders [9]. In addition, 47% of these articles described UTI being involved in exacerbating or even precipitating these conditions [9].…”
Section: Discussionmentioning
confidence: 99%
“…Where does blood endotoxin come from? Active bacterial infections may produce endotoxin, and for example, urinary tract infections are associated with dementia, delirium and other neuropsychiatric disorders [35]. However, in the absence of infection, endotoxin still crosses the mucosal membranes of gut, gums, nose or lungs, the main source being intestinal permeability [36, 37].…”
Section: Serum Endotoxinmentioning
confidence: 99%
“…It is appreciated that the aging brain may be more vulnerable to pathological changes in response to acute illness and infections. For example, urinary tract infections, which are not associated with cognitive symptoms in the young, can cause delirium and other neuropsychiatric conditions in the elderly [49]. Rodent models also suggest that aged mice have more severe neuroinflammatory responses and exacerbated behavioral outcomes following peripheral immune stimuli [50].…”
Section: Age-associated Changes In Neuroimmune Functionsmentioning
confidence: 99%